Strategi Work-Family Balance pada Perempuan Suku Banjar yang Memiliki Peran Ganda - Yulia Hairina; Mahdia Fadhila (Jurnal Studia Insania, 2018)
This study aims to determine work-family balance strategies in women who have a dual role especially in Banjar women and to know the factors that influence the achievement of balanced work family. The method used is descriptive qualitative, with interview data collection methods. The research subjects were selected by using purposive sampling technique. The results of the study are related to strategies in balancing work and family that are done by the subject, namely 1) making the best use of time, time management, completing work on time, separating work and family matters, making special schedules to spend with children and other family members every Saturday Sunday or holiday, and prioritize important days for families and children such as child shows and others that indeed our existence becomes important for our families 2) monitor the family while working for example by making a single call to the child to check the situation even there are parents or household assistants who guard them, 3) share roles with husbands. Furthermore, the factors that influence the achievement of balance are 1) partner support 2) commitment at the beginning of marriage 3) the same experience of the husband. The implication of this study is that it can provide an overview related to work-family balance strategies in women who have multiple roles. Work-family balance is important for everyone because if the multiple roles run are not balanced then it is likely to lead to family and work conflicts.